A ESCOLARIZAÇÃO DO ALUNO COM SÍNDROME DE DOWN E O ENSINO ESPECIALIZADO - ASSAF, DANIELLE LUETH (2017)
This research aims to expand the understanding about a theme that is gaining prominence in our society, day after day: the inclusion of people with disabilities. With the new public policies, a constant updating is necessary, aiming at the improvement of the quality of the experience of disabled people in the school environment and the expansion of their learning capacity. Although the theme is not new, with the advent of the Magna Carta, and the fundamental rights and guarantees of the citizen, a new systematics has been inevitable to deal with this issue. It is a controversial topic and therefore specific field research was required. There is great divergence among professionals: in favor, against or partially against total or partial inclusion. There are, therefore, those who stand up for the insertion of these children into specialized institutions or the presence of specific classrooms for all students who have some type of disability. Thus, the present work aimed at the following objectives: to reflect on the public policies of inclusive education and its applicability in the reality of Brazilian education; Understand aspects inherent to Down Syndrome, such as etiology and characteristics, as well as aspects of development and learning; To seek, understand and reflect on pedagogical practices that aim to aid in the learning process of students with Down Syndrome; And reflecting on the learning conditions offered to these students by regular education and how specialized education can contribute. For the development of the following work, it was necessary a bibliographic review in the desired area, field research in a specialized school, collection of historical data, collection of data through interviews and testimonies and, finally, the analysis of the data obtained in the research with the school, emphasizing that the methodology used was the qualitative method, through interviews conducted with semi-structured questionnaire and observation of the context, as mentioned above. It is important to mention that the montessorian pedagogy was investigated, bringing significant benefits to the learning of the students with Down's syndrome, through the adaptation of the method.